Influence of GlycoGag on the Incorporation of Host Membrane Proteins Into the Envelope of the Moloney Murine Leukemia Virus - Maltseva, Mariam; Langlois, Marc-André (Frontiers in Virology, 2021)
Analysis of viral particle heterogeneity produced from infected cells has been limited by the inefficiency of traditional analytical methods to characterize large populations of viruses at an individual particle level. Flow virometry (FVM) is an emerging technique based on flow cytometry principles that enables a high throughput, multiparametric, and phenotypic characterization of viruses at a single particle resolution. Here, we performed FVM to analyze surface markers found on Murine Leukemia Virus (MLV) and glycosylated Gag-deficient (glycoGag) MLV. The glycoGag viral accessory protein has several roles in the MLV viral infection cycle including directing retroviral assembly and particle release at lipid rafts. Based on previous studies, we hypothesize that glycoGag modulates host protein incorporation into the viral envelope during viral assembly and budding. Here, by using FVM, we reveal that glycoGag is associated with an increased incorporation of the host-derived tetraspanins CD81 and CD63 along with the lipid raft marker and immune antigen Thy1.2 during the assembly and release of viral particles from NIH 3T3, EL4, and primary CD4+ T cells. Moreover, we show differences in the uptake of host proteins by viruses that are released from the two cell lines and primary T lymphocytes in similar proportions to the expression levels on the infected cells. Additionally, at the individual viral particle level, we observed a certain degree of expression heterogeneity of host-derived antigens within the viral population. Finally, certain cellular antigens can show either enrichment or exclusion from the viral envelope depending on whether glycoGag is expressed by the virus. This suggests that glycoGag is involved in a mechanism of selective host protein incorporation.